FOLK VOCAL AND CONTEMPORARY MUSIC: FROM ETHNO-JAZ TO ELECTRONICS - Коломицева, Марія; Марчун, Оксана (SWorldJournal, 2025)
Folk vocals are one of the oldest forms of musical expression, formed in the context of cultural traditions, ritual practices and social communication. Folk songs performed the functions of knowledge transfer, calendar regulation, ritual invocation and fo